Культивування Murraya exotica L. у захищеному ґрунті - Boyko, L.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The results of study of Murraya exotica L. ontogenesis in the conditions of the protected soil of Kryvyi Rih Botanical Garden of the NAS of Ukraine are given.